Analysis of the Risk Management System for Company Performance Through Corporate Governance in PT. Permodalan Nasional Madani Surabaya Regional - Dewianawati, Dwi; Setiawan, Erry (Jurnal Ekonomi, 2024)
This study aims to evaluate the influence of risk management and the application of Corporate Governance principles on the performance of PT Permodalan Nasional Madani (PNM) Regional Surabaya, as well as to examine the role of Corporate Governance as a mediator in the relationship between risk management and company performance. This study uses a quantitative approach with the path analysis method to understand the relationship between variables. The results of the study reveal that risk management has a significant positive impact on company performance. These findings show that a company's ability to effectively identify and manage risks contributes to improved performance. In addition, Corporate Governance has also been proven to have a positive and significant effect on the company's performance, indicating that the implementation of good governance principles is able to support the improvement of operational and financial performance. Furthermore, Corporate Governance acts as an important mediator that strengthens the relationship between risk management and company performance. With the implementation of good governance, risk management can be optimized to support the achievement of superior performance.